Multiple harmonic frequencies resonant cavity design and half-scale prototype measurements for a fast kicker - Huang, Yulu; Wang, Haipeng; Rimmer, Robert A.; Wang, Shaoheng; Guo, Jiquan (Physical review. Accelerators and beams, 2016)
Quarter wavelength resonator (QWR) based deflecting cavities with the capability of supporting multiple odd-harmonic modes have been developed for an ultrafast periodic kicker system in the proposed Jefferson Lab Electron Ion Collider (JLEIC, formerly MEIC). Previous work on the kicking pulse synthesis and the transverse beam dynamics tracking simulations show that a flat-top kicking pulse can be generated with minimal emittance growth during injection and circulation of the cooling electron bunches. This flat-top kicking pulse can be obtained when a DC component and 10 harmonic modes with appropriate amplitude and phase are combined together. To support 10 such harmonic modes, four QWR cavities are used with 5, 3, 1, and 1 modes, respectively. In the multiple-mode cavities, several slightly tapered segments of the inner conductor are introduced to tune the higher order deflecting modes to be harmonic, and stub tuners are used to fine tune each frequency to compensate for potential errors. In this paper, we summarize the electromagnetic design of the five-mode cavity, including the geometry optimization to get high transverse shunt impedance, the frequency tuning and sensitivity analysis, and the single loop coupler design for coupling to all of the harmonic modes. In particular we report on the design and fabrication of a half-scale copper prototype of this proof-of-principle five-odd-mode cavity, as well as the rf bench measurements. Finally, we demonstrate mode superposition in this cavity experimentally, which illustrates the kicking pulse generation concept.